PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN PROMOSI TERHADAP PROSES KEPUTUSAN PEMBELIAN HANDPHONE SAMSUNG DI SEMARANG - Masazid, 13.05.51.0018; Sholiha, Euis (Students' Journal of Economic and Management, 2018)
This study aims to examine the effect of product quality, price perceptions and promotion of Samsung Mobile purchasing decision process in Semarang. The population in this study is the whole society of Samsung mobile users in Semarang. The number of samples studied is as many as 100 people selected in accordance with the criteria as respondents by using sampling technique purposive sampling. Data collection method used in this research is using questionnaire method filled by respondents. Analytical techniques used in this study are validity test, reability test, multiple linear regression test, model test, simultaneous significant test, hypothesis test. Data processing using SPSS Version 18. The results of this study indicate that product quality, price perception, and promotion have a positive and significant influence on the purchasing decision process.Keywords: product quality, price perception, promotion and purchasing decision process